Exploring the prevalence and predictors of overweight and obesity in second cycle schools in Ghana - Amponsem-Boateng, Cecilia; Oppong, Timothy Bonney; Amertil, Ninon P.; Boakye-Yiadom, Jonathan; Kpongboe, Doris Grace (International Journal Of Community Medicine And Public Health, 2024)
Background: Overweight and obesity have become pressing global public health concerns, with their prevalence steadily increasing in many countries, including Ghana. The burden of these conditions is not limited to adults. Second-cycle schools play a crucial role in shaping the physical and mental well-being of students, making it imperative to understand the prevalence and predictors of overweight and obesity in this specific demographic. This study, therefore, seeks to estimate the prevalence of overweight and obesity and the predicting factors in students in second-cycle schools in Ghana. Methods: A cross-sectional survey was conducted in selected second-cycle schools in the Eastern, Ashanti, and Brong Ahafo Regions of Ghana from January 31st, 2019 to December 20th, 2021. The sample was determined using an assumed minimum sample of 206 people with an overweight or obesity prevalence of 15%. Two schools were picked by lottery from the list of the three districts that were selected from each region. This investigation comprised six (6) second-cycle institutions. Results: Overall, 1086 students participated in this study. 43.74% and 56.26% females. The prevalence of obesity and overweight was 28.17%. Overweight (24.95%) and obesity (3.1%). 16.20% (female) and 11.97% (male). BMI (female-gender) and type of food (cooked at home) are predictive factors. Conclusions: Predictive factors included BMI, gender (female), and homemade foods. Educating students and the general public on the risks of obesity and helping curb the misconception of overweight and obesity as a sign of ‘good living’ and beauty within Ghanaian communities is recommended.